Cesium removal from wastewater: High-efficient and reusable adsorbent K1.93Ti0.22Sn3S6.43. (October 2022) - Jiang, Zhenzhen; Liu, Gaoling; Ma, Chi; Guo, Yafei; Duo, Ji; Li, Mingli; Deng, Tianlong
Abstract: Efficient and quick removal of radioactive Cs + from wastewater is significant for the safe use of nuclear energy and human health. A novel adsorbent K1.93 Ti0.22 Sn3 S6.43 (KTSS) was developed for Cs + removal from complex natural water systems. The working mechanism of KTSS for removing Cs + was the synergistic effect of ion exchange and the Cs⋯S binding, which was proved by several characterization techniques. KTSS showed ultrafast kinetics for Cs + adsorption within 1 min with a removal rate of 99%. Meanwhile, KTSS exhibited a higher adsorption capacity of 450.12 mg/g than many other adsorbents to remove Cs + and possessed excellent chemical stability in a wide pH range of 3–12. Thanks to the natural affinity arising from the S 2− ligands, KTSS displayed excellent selectivity for Cs + even in different complex water systems. The separation factors between Cs + and the coexisting ions of Na +, K +, Mg 2+, Ca 2+ were ranged from 408.61 to 7448.20. Fortunately, by eluting with NaNO3 the adsorbent could realize the green regeneration and cyclic utilization. Furthermore, it was found that KTSS had tremendous advantages in the removal of Cs + in comparison with the other adsorbents. Consequently, it should be considered that KTSS obtained in this study has great potential in applying ultrafast and high-efficient removal of Cs + from wastewater. Graphical abstract: Image 1 Highlights: Novel adsorbent K1.93 Ti0.22 Sn3 S6.43 (KTSS) was developed for Cs + removal from wastewater for the first time. KTSS has characteristics of ultrafast, high-efficient Cs + removal and good cycling performance. Several characterization techniques revealed the Cs +  removal mechanism of KTSS. KTSS shows an excellent application prospects for Cs +  removal from wastewater.